Management Model of Zakat Collection at the Badan Amil Zakat Nasional in the Province of West Sumatra Indonesia - Nopiardo, Widi; Asrida, Asrida; Elfadhli, Elfadhli (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Effective and efficient zakat management requires good coordination between various parties. This research aims to analyze how coordination between the Provincial Badan Amil Zakat Nasional and the district or city Badan Amil Zakat Nasional in zakat collection activities. This research uses qualitative method with case study approach. Data sources were taken from ten informants from the Badan Amil Zakat Nasional of district or city through in-depth interviews selected using purposive sampling technique to all informants. All data were analyzed using the analysis technique proposed by Miles and Huberman. The results of the analysis show that coordination activities can be carried out because of good coordination planning. First, the annual regional coordination meeting. Second, coordination through official letters in the form of sending documents or letters between the Badan Amil Zakat Nasional of district or city in West Sumatra. Third, coordination through direct communication. The benefit of this research is that it is taken into consideration by the Badan Amil Zakat Nasional throughout West Sumatra to strengthen the coordination aspects of collection.